Judicial Legislation: Retreat From Anns. - Aylmerton, The Rt Hon Lord Oliver of (Journal of Malaysian and Comparative Law, 1989)
Text of the Third Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya and the British Council) delivered by the Rt. Hon. Lord Oliver of Aylmerton, P.C. on September 12, 1988 in the presence of His Royal Highness, Sultan Azlan Shah, Sultan of Perak.